Bittersweet - McCullough, Colleen, 1937-2015 (Simon & Schuster, 2014)
"Returning to the sweeping romantic saga, Colleen McCullough presents a new major work: the story of four unforgettable sisters navigating work, love, and their dreams in 1920s Australia. Because they are two sets of twins, the four Latimer sisters are as close as can be. They are famous throughout New South Wales for their beauty, wit, and ambition, but as they step into womanhood, they are not enthusiastic about the limited prospects life holds for them. Instead, Edda wants to be a doctor, Tufts wants to organize everything, Grace won't be told what to do, and Kitty wishes to be known for something other than her beauty. Together they decide to enroll in a training program for nurses--a new option for women of their time. As they become immersed in hospital life and the demands of their training, they meet people and encounter challenges that spark new maturity and independence. They meet men from all walks of life--the local farmers, their professional colleagues, and even men with national roles and reputations, and each sister must make decisions about what she values most. The results are sometimes happy, sometimes heartbreaking, but always...bittersweet"--